PELAKSANAAN PROSEDUR PROTOKOLER COVID-19DALAM MELAYANI TAMU DISUSHI TEI RESTORAN DI MEDAN SUMATERA UTARA - Nirwaty Tarigan; Naomi Serlina Agave Naomi Serlina Agave (Akademi Pariwisata Darma Agung, 2020)
All companies engaged in food and beverage, especially Sushi Tei Restaurants are required to have special procedures in terms of handling food and beverage processing, serving and serving to customers amid the COVID-19 outbreak, this is useful for creating a comfortable and safe feeling for customers who will buy. products from the restaurant, the procedure must be carried out consistently and properly. As for the focus of the research is the special procedures used in serving guests. This research was conducted to determine the COVID-19 protocol procedure in serving guests at Sushi Tei Restaurant in Medan, North Sumatra, knowing the seating distance between guests and whether there is a divider or partition between the tables according to the health protocol for restaurants issued by the Minister of Health of the Republic of Indonesia . The research was conducted from May 1, 2020 to June 30, 2020. The population in this study were 3 Cashiers, 2 Greeters, 8 Waiters, and 1 Bushboy, so the sample in this study was 14 people. From the conclusions, the authors provide suggestions which later can be taken into consideration for the restaurant, so that the service quality of Sushi Tei Restaurant can be maintained.